ANALISIS PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Staff PT TASPEN (PERSERO) Kantor Cabang Utama Semarang) - Setiaji, Apriyanto; Djastuti, Indi (Diponegoro Journal of Management, 2015)
Development of a service industry not only promote the quality, timeliness and quality of service, but also requires the management of human resource is appropriate. This can be improved by considering factors such as, transformational leadership style, work motivation and organizational commitment. This study aims to explain how the effect of transformational leadership style, work motivation and organizational commitment to employee performance at PT TASPEN (Persero) Main Branch Office in Semarang.The population used in this study were all staff employees PT TASPEN (Persero) Main Branch Office in Semarang, amounting to 60 people. The sampling technique was conducted by sampling saturated. The analytical method used is multiple regression analysis. The results of research to get the regression equation as follows: Employee Performance = -0,145X1 + 0,542X2 + 0,307X3Based on the test instrument, the indicators are valid and reliable. In the classical assumption, there are no symptoms multicoloniarity, does not occur heterokedastisitas, and normal distribution of data. The coefficient of determination shows the figure of 0,439, which means that the variable of employee performance is influenced by variables of transformational leadership style, employee motivation and organizational commitment of 43.9%. The results showed that work motivation and organizational commitment positive and significant impact employees performance of PT TASPEN (Persero) Main Branch Office in Semarang either partially or simultaneously. While the results of research on transformational leadership style negative and not significant impact employees performence of PT TASPEN (Persero) Main Branch Office Semarang.